Molecular and Self‐Trapped Excitonic Contributions to the Broadband Luminescence in Diamine‐Based Low‐Dimensional Hybrid Perovskite Systems. Issue 20 (26th July 2018) - Krishnamurthy, Shrreya; Naphade, Rounak; Mir, Wasim J.; Gosavi, Suresh; Chakraborty, Sudip; Vaidhyanathan, Ramanathan; Ogale, Satishchandra
Abstract: The present solid state lighting (SSL) technology is based on using a combination of phosphors to give the desired white light emitting devices. The property of broadband emission from a single phosphor is not only difficult to achieve but also poses a challenge in device fabrication. Hybrid organic–inorganic perovskites especially in low dimensions (2D/1D) are being widely explored for their optoelectronic properties. Few of these materials exhibit broadband emission upon ultraviolet excitation, providing a scope for synthetic engineering in achieving commercially viable single‐phosphor materials. In this work, three interesting diammonium‐based low‐dimensional hybrid perovskites for broadband photoluminescence (PL) are examined. The doubly protonated ethylenediamine‐configured monoclinic ( P 21 / n ) 1D ribbon assembly (H3 NCH2 CH2 NH3 )8 (Pb4 Br18 ) · Br6 (1 ) and the orthorhombic ( Pbcm ) 2D‐twisted octahedral (H3 NCH2 CH2 NH3 )(Pb2 Cl6 ) (2 ) show white luminescence, while the doubly protonated piperazine‐configured orthorhombic ( Pnnm ) 0D dual‐octahedral (C4 N2 H12 )4 (Pb2 Br11 ) · (Br)(H2 O)4 (3 ) exhibits bluish‐white luminescence. Based on the PL of the organic diammonium salt, the time‐resolved PL, Raman signatures, and density functional theory (DFT) calculations, it is shown that the broadband luminescence has dual origin: one around 400 nm from diammonium‐related molecular fluorescence and another around 516 nm from self‐trapped excitons. The structure‐specific relative contributions and interplay between the two define the overall character of the broadband luminescence. Abstract : White light emitting hybrid perovskites are an emerging class of promising materials for solid state lighting devices. The mechanism leading to broadband emission is known to arise from self‐trapping of excitons due to structural distortions. Small molecule engineering is being used as a tool to understand the role of organic moiety in contribution to this broadband luminescence.